2009
DOI: 10.1155/2009/106145
|View full text |Cite
|
Sign up to set email alerts
|

The Levels of Tumor Necrosis Factor-Alpha and Interleukin-6 in Patients with Isolated Coronary Artery Ectasia

Abstract: Background/Aim. Coronary artery ectasia (CAE) is considered as a variant of atherosclerosis. Tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6) are among the sensitive markers of systemic inflammation. The aim of this study was to evaluate the plasma levels of the cytokines; TNF-α and IL-6 in CAE patients. Methods. Plasma concentrations of TNF-α and IL-6 were measured in 36 patients with CAE (28 males, mean age: 58.2 ± 12 years), and results were compared with age and sex-matched controls (n = 32) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 20 publications
0
32
0
2
Order By: Relevance
“…However, some investigations assessing the role of inflammation in adult patients with coronary artery ectasia were conducted, and these studies reported higher levels of serum (IL)-6 and (TNF)-α, together with the accumulation of inflammatory cells in the medial layer of coronary arteries (27)(28)(29). Some other studies additionally found higher neutrophil to lymphocyte ratios in patients with coronary artery ectasia than in healthy controls, and they denoted that neutrophils cause important changes in vascular tissue by release of elastase, myeloperoxidase, free-oxygen radicals, and various hydrolytic enzymes (11,30).…”
Section: Discussionmentioning
confidence: 99%
“…However, some investigations assessing the role of inflammation in adult patients with coronary artery ectasia were conducted, and these studies reported higher levels of serum (IL)-6 and (TNF)-α, together with the accumulation of inflammatory cells in the medial layer of coronary arteries (27)(28)(29). Some other studies additionally found higher neutrophil to lymphocyte ratios in patients with coronary artery ectasia than in healthy controls, and they denoted that neutrophils cause important changes in vascular tissue by release of elastase, myeloperoxidase, free-oxygen radicals, and various hydrolytic enzymes (11,30).…”
Section: Discussionmentioning
confidence: 99%
“…Koroner arter ektazisi sıklığı farklı anjiyografik serilerde %0.2 ile %10 arasında rapor edilmiştir (1,3,15,18,19). Bizim çalışma-mızda KAE sıklığı %5.6 idi.…”
Section: Discussionunclassified
“…Bunu sol ön inen arter ve sirkumfleks arter izler. Ana koroner arterde ektazi oldukça nadirdir (1,19,20). Sıklığı açısından bizim çalışmamızda -da literatürde belirtildiği gibi-KAE en sık sağ koroner arterde görülmektedir (LAD, CX ve RCA için sırası ile %25, 33 ve 42) (1,3,15,(18)(19)(20).…”
Section: Discussionunclassified
“…CA detected in 0.3%-5.3% of consecutive angiographic studies (3,4). Etiology of CA include atherosclerosis (%50), congenital anomalies (20%-30%), syphilis, polyarteritis nodosa, Takayasu arteritis, Kawasaki disease, scleroderma, Ehlers-Danlos syndrome, trauma (percutaneous coronary intervention), bacterial and mycotic infections, nitrite and herbicide products exposure (5), and other rare causes such as adult polycystic kidney disease (6).…”
Section: Discussionmentioning
confidence: 99%